2018
DOI: 10.1038/s41433-018-0210-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among different diagnostic criteria for chronic ocular graft-versus-host disease applied with and without pre-transplant ophthalmological examination

Abstract: The diagnosis of ocular GVHD varied significantly in our cohort of hematological patients according to both the diagnostic criteria used and the visit protocols applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
(40 reference statements)
0
9
0
1
Order By: Relevance
“…An extension of the Tear Film and Ocular Surface Society Dry Eye Workshop II (TFOS DEWS II) criteria originally meant for conventional DED has been recently advocated for diagnosing oGVHD in patients undergoing allo-HSCT[ 26 ] according to which any new positivity or worsening of the existing disease after allo-HSCT may be considered to be sufficient for diagnosing oGVHD. Diagnosis required ocular surface discomfort symptoms with OSDI score ≥13 along with any one of the following; TFBUT <10 s; tear osmolarity >308 mOsm/L in either eye (or an inter-eye difference >8 mOsm/L); ocular surface staining (>5 corneal spots, >9 conjunctival spots or lid wiper epitheliopathy of ≥2 mm in length and/or ≥25% sagittal width).…”
Section: Current Perspectives On Ogvhd Diagnostic Criteria Definition and Gradingmentioning
confidence: 99%
See 1 more Smart Citation
“…An extension of the Tear Film and Ocular Surface Society Dry Eye Workshop II (TFOS DEWS II) criteria originally meant for conventional DED has been recently advocated for diagnosing oGVHD in patients undergoing allo-HSCT[ 26 ] according to which any new positivity or worsening of the existing disease after allo-HSCT may be considered to be sufficient for diagnosing oGVHD. Diagnosis required ocular surface discomfort symptoms with OSDI score ≥13 along with any one of the following; TFBUT <10 s; tear osmolarity >308 mOsm/L in either eye (or an inter-eye difference >8 mOsm/L); ocular surface staining (>5 corneal spots, >9 conjunctival spots or lid wiper epitheliopathy of ≥2 mm in length and/or ≥25% sagittal width).…”
Section: Current Perspectives On Ogvhd Diagnostic Criteria Definition and Gradingmentioning
confidence: 99%
“…The influence of a pre-allo-HSCT evaluation on diagnostic performance seems to be much more for NIH and ICCGVHD criteria emphasizing that majority of pre-allo-HSCT DED cases were due to tear film instability. [ 26 ] Pre-allo-HSCT evaluation for DED is now widely recommended to help differentiate between preexisting dry eye and the new-onset DED diagnosed as oGVHD post-allo-HSCT.…”
Section: Current Perspectives On Ogvhd Diagnostic Criteria Definition and Gradingmentioning
confidence: 99%
“…Giannaccare, et al showed that dry eye is already present in a large percentage of patients with hematologic disease before HCT. 80 Early diagnosis is key to control of symptoms and ultimately managing the clinical signs. Recent research is focused on advancements in prophylaxis, diagnostic criteria, and treatment.…”
Section: Overview Of Chronic Ogvhdmentioning
confidence: 99%
“…This approach allows for better coordination between care team providers. 17,[115][116][117][118] Anecdotally, artificial lubricants and 0.05% cyclosporine-A (CsA) are usually the treatment of the first choice for hematologists/oncologists. A longitudinal, prospective, non-randomized small study of 20 transplant patients was pre-treated with CsA twice daily for 12 months after transplant.…”
Section: Management Of Chronic Ogvhdmentioning
confidence: 99%
“…Tear biomarkers in oGVHD have focused mainly on the role of cytokines [8,10,[14][15][16][17] and less on protein profiling to find candidate proteins that can be associated with the disease [18,19]. All these previous studies have been performed on post-HSCT patients, whereas ocular surface changes and high DED prevalence were shown already before HSCT [20,21]. This had suggested that a pre-HSCT ocular surface assessment is recommended for early DE management and appropriate evaluation of post-HSCT changes [6].…”
Section: Introductionmentioning
confidence: 99%